Essays on abdominal combat trauma surgery / V. Bely, Y. Zarutskyi, S. Aslanyan. - Kyiv: Ludmila, 2021. - 303 p. - V. I. Desyateryk (Клінічна хірургія, 2022)
Essays on abdominal combat trauma surgery / V. Bely, Y. Zarutskyi, S. Aslanyan. - Kyiv: Ludmila, 2021. - 303 p.